Studies on stem cuttings of kiwi (Actinidia chinensis PL. CV Bruno) - Ono, E. O. (2000)
The work was carried out to study the effects of some auxins and boron in the rooting of kiwi (Actinidia chinensis Planch cv Bruno) stem cuttings.. These cuttings were treated on the base individually with H2O; NAA 300 mg.L-1 IBA 300 mg.L-1; NAA 300 mg.L-1 + Boron; IBA 300 mg.L-1 + Boron; NAA 0,5%-talc and IBA 0,5%-talc. After the treatments, the cuttings were placed in styrofoam trays with vermiculite under moist conditions for 120 days. The evaluation of auxin and boric acid effects were made by observing rooted stem cuttings percentage; reducing and total sugar analysis (g/100 g of dry matter); and tryptophan analysis (in mu g/100 mg of dry matter). The effects of such treatments were observed during four seasons of the year. The results showed that summer season was the best for rooting. Use of IBA or NAA in the cuttings showed to be unnecessary.